Long-term effect of everolimus in recurrent thymic neuroendocrine neoplasia - Lang, Matthias; Hackert, Thilo; Anamaterou, Chrysanthi (Clinical endocrinology, 2021)
Purpose Neuroendocrine neoplasia (NEN) of the thymus is a very rare entity with a poor prognosis. None of the treatments was proofed by studies. Usually, therapy protocols for bronchopulmonary carcinoids are used. So far no data exist on the effect of mammalian target of rapamycin (mTOR) inhibitors. We describe our long-term experience with everolimus and give a thorough review of the therapeutic strategies used so far. Patients and Methods Four patients (mean age 46 years, range 37-55) with progressing thymic NEN (t-NEN) (two well-differentiated atypical carcinoids and two atypical carcinoids with large cell characteristics) were treated with everolimus 10 mg/day after the failure of at least one previous medical therapy. Everolimus was applied after a mean interval of 32.4 months (range 5-56) after the first diagnosis. The follow-up included clinical examination, imaging and chromogranin A testing in 3 or 6 monthly intervals. Results We observed stable disease for a mean of 20.8 months. Both patients with large cell characteristics t-NEN (Ki-67 of 20%) had rapid progress after 7 and 10 months and had more previous therapies (three and six) than the patients with well-differentiated t-NEN (Ki-67 5% and 10%, progress after 24 and 42 months, one and two previous therapies). No severe side effects occurred. In three of four patients, everolimus led to stable disease for the longest compared to the other nonsurgical therapies used. Conclusion Comparing the sparse data available everolimus is a promising treatment for t-NEN at least in second-line therapy. A low Ki-67 index was associated with a better outcome.